ANALISIS PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN TO DEPOSIT RATIO (LDR), BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), DAN CADANGAN PENGHAPUSAN KREDIT TERHADAP KREDIT BERMASALAH (NON PERFORMING LOAN) BANK UMUM di INDONESIA 2009-2015: ANALISIS DATA - Wandadari, Dyah Ayu (Jurnal Ilmiah Mahasiswa FEB, 2015)
Bank is a part of financial institutions which have intermediation function which is collecting fund from people and distribute it back into loan. Loan which distribute by bank have potentially make non performing loan, because the more loan being distributed the more credit problem will be held by the bank. This research have purpose to know how the influence of CAR, LDR,BOPO, and also proposal of Eliminating non performing Loans in ordinary bank in indonesia. This research sample is using 5 bank that have highest asset and method that use panel data methods. Independent variable which is used in this research is CAR, LDR,Â  BOPO and proposal of Elimination of non performing loans. The disscussion result of this research show that simultantly , independent variable affect significantly to Non performing loans. The Result partialy test showed that CAR, LDR, BOPO and the proposal of elimination of non performing loans affected significantly and positively into Non performing loansÂ  Kata Kunci: Non Performing Loan, CAR, LDR, BOPO, the proposal of elimination of non performing loans (PPAP)